DETEKSI GEJALA DEPRESI PADA IBU PASKA MELAHIRKAN DI POLIKLINIK KEBIDANAN RSUD DR. RASIDIN KOTA PADANG - Rani Rahmawati B; Mutiara Anissa; Primadella Sagita (Nusantara Hasana Journal, 2025)
Childbirth and the addition of family members is a generally pleasant but stress-inducing event. If not handled properly, postpartum mothers can be indicated to have postpartum depression. Therefore, it is very necessary to do early detection of postpartum depression symptoms to prevent mothers from experiencing depression by using the Edinburgh Postnatal Depression Scale (EPDS) questionnaire, so that it is hoped that the postpartum depression rate can be eliminated. To detect depressive symptoms in postpartum mothers who come to control at the Obstetrics Polyclinic of RSUD dr. Rasidin in Padang. This study used a categorical descriptive method using primary data and using a sampling method, namely a consecutive sampling technique with a total sample of 52 postpartum mothers. 52 of postpartum mothers most were at the age of 20-35 years as many as 37 people (71.2%), not working which was 42 people (80.8%), education level was high school graduation which was 33 people (63.5%), type of cesarean delivery was 47 people (90.4%), parity history was multiparous which was 41 people (78.8%) and no postpartum depression was detected as many as 48 people (92.3%). Many mothers are not detected postpartum depression at the Obstetrics Polyclinic of RSUD dr. Rasidin in Padang.